Konflik Sosial Nelayan Penerima Bantuan Rumah Layak Huni Di Kecamatan Simeulue Timur Kabupaten Simeulue - Asni, Nur; Tjoetra, Afrizal (Indonesian Journal Publisher, 2025)
This study examines social conflicts arising from the poverty alleviation program through the provision of livable housing assistance for fishermen families in East Simeulue District, Simeulue Regency. The research aims to identify the sources of social conflict among fishermen receiving and not receiving housing assistance and to analyze the mechanisms used to resolve these conflicts. Grounded in Ralf Dahrendorf’s conflict theory, this study employs a qualitative method with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving fishermen, community leaders, and local government representatives. The findings reveal that social conflicts emerged due to feelings of exclusion and unequal treatment experienced by fishermen who did not receive assistance, scarcity of resources, inadequate communication regarding program rules and eligibility criteria, and ineffective leadership characterized by unfair decision-making. Additionally, social jealousy and the presence of provocateurs within the fishing community intensified tensions. Conflict resolution was conducted through deliberative processes emphasizing communication facilitation between conflicting parties, primarily through arbitration and mediation as third-party interventions. Furthermore, local wisdom known as “salah manyamba” gawai mangisi” played a significant role in resolving disputes by involving respected community figures and prioritizing family-based deliberation. In conclusion, the study highlights the importance of transparent governance, effective communication, and the integration of local wisdom in minimizing social conflict and ensuring the equitable implementation of poverty alleviation programs in coastal communities.